Correlation between Waist Circumference and IGF-1 Levels in an Elderly Population in Bali, Indonesia - I Made Pande Dwipayana; Wira Gotera; Made Ratna Saraswati; I Made Siswadi Semadi; Ida Bagus Aditya Nugraha; Ketut Suastika; Anak Agung Gde Budhiarta; Padma Amrita; Wahyu Pratama Putra (Journal of the ASEAN Federation of Endocrine Societies)
Background. Hyperinsulinemia due to insulin resistance is hypothesized to act as a promotor of cancer growth. In addition to the direct effects of hyperinsulinemia on cancer cells, the stimulation of tumor cell growth can also be indirectly mediated through growth factors and receptors such as insulin-like growth factor 1 (IGF-1). Increased cancer risk is also associated with increased adipose tissue, such as in abdominal obesity, due to the higher risk of insulin resistance and hyperinsulinemia. Waist circumference is a parameter that indicates an individual's level of adiposity. In addition, the risk of cancer also increases in the elderly as they age. This study aims to assess the correlation between waist circumference and IGF-1 levels in the elderly population in Bali, Indonesia.